2017
DOI: 10.1021/acs.langmuir.7b00898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Thermocouple on Measuring the Temperature Discontinuity at a Liquid–Vapor Interface

Abstract: The coupled heat and mass transfer that occurs in evaporation is of interest in a large number of fields such as evaporative cooling, distillation, drying, coating, printing, crystallization, welding, atmospheric processes, and pool fires. The temperature jump that occurs at an evaporating interface is of central importance to understanding this complex process. Over the past three decades, thermocouples have been widely used to measure the interfacial temperature jumps at a liquid-vapor interface during evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
1
11
1
Order By: Relevance
“…The temperature jumps were larger at lower pressures and were strongly dependent on the heat flux from the vapor side 26 , 27 . The measured temperature jumps were inconsistent with the prevailing kinetic theory of gases that would predict a 10–20 times smaller temperature jump under the same condition 27 , 28 . To tackle such a discrepancy, statistical rate theory (SRT) of evaporation was applied 29 , 30 .…”
Section: Introductioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The temperature jumps were larger at lower pressures and were strongly dependent on the heat flux from the vapor side 26 , 27 . The measured temperature jumps were inconsistent with the prevailing kinetic theory of gases that would predict a 10–20 times smaller temperature jump under the same condition 27 , 28 . To tackle such a discrepancy, statistical rate theory (SRT) of evaporation was applied 29 , 30 .…”
Section: Introductioncontrasting
confidence: 89%
“…If experiments are performed in the limit of evaporation that is mainly governed by heat transfer, as was the case in most of previous studies, the conclusions about these concepts may not be accurate since the interfacial phenomena have not played a role in evaporation from the interface. This is perhaps the reason that the SRT expression for evaporation flux agrees with a wide range of temperature jumps 28 , or that the evaporation coefficients obtained from the experiments are highly scattered between zero and one 49 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Possible factors affecting the measurement of the interfacial temperature discontinuity, including radiation and evaporative cooling of the thermocouple bead, were closely examined and concluded to be negligible. Various scientists conducted these experiments and reported temperature discontinuity of 0.14–28 K. ,, Although the majority of experiments indicated that the liquid side of the interface is colder than the vapor side, few experiments , showed the opposite direction of temperature discontinuity. This temperature discontinuity at an evaporating water interface remains still a mystery.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of different types of thermocouples has been developed, covering a wide range of temperatures and work environments. [ 7–10 ] Typically, in order to achieve on‐chip thermometry with conventional thermocouples, two separate fabrication runs are required.…”
Section: Introductionmentioning
confidence: 99%